Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The institutions Sociedad Colombiana de Ciencias Hortícolas (SCCH), Universidad Pedagógica y Tecnológica de Colombia (UPTC) and Universidad Francisco de Paula Santander (UFPS), editors of Revista Colombiana de Ciencias Hortícolas, wish to inform our authors and readers that we continue to take giant steps in implementing all necessary changes for maintaining the recognition gained by the Department through Revistas Científicas Colombianas Especializadas – Publindex (Colciencias) in Convocatoria 830 of 2018, which classifies our journal in Category B, and for improving our journal’s classification as much as possible. For this reason, the members of the Editorial Committee will strive to ensure that the quality of the published articles will contribute to achieving this important goal. As such, we are very pleased to present to our readers volume 13 number 3 (2019), which contains 14 articles, available completely in English in a digital format with continuous publication, i.e. accepted versions are published subject to change by definitive versions. However, a printed copy of this issue will be maintained for legal and administrative purposes.